Advancing endoscopic traction techniques in endoscopic submucosal dissection - Khan, Suliman; Ali, Faisal S.; Ullah, Saif; Huang, Xue-; Li, Hongyu (Frontiers in Oncology, 2022)
Traction techniques have emerged as a desirable “second-hand” while performing endoscopic submucosal dissection (ESD), enabling adequate visualization of submucosal tissue and vasculature, which allows for safe and efficient dissection. Multiple traction techniques have been developed over the years, and these can be broadly divided into internal and external traction techniques. This arsenal of techniques allows for traction that is personalized to the location of the lesion undergoing ESD. Although a welcomed assistant, mastering traction techniques requires adequate training, resource availability, and a thorough understanding of the shortcoming of each technique. The advent of robot-assisted endoscopic technology ushers in a new era of ESD, and with it come its own unique challenges that remain to be elucidated. Future research and development efforts need to focus on pathways and curriculums for trainees to master the currently available endoscopic traction techniques and provide avenues for the development of newer traction modalities.